2000
DOI: 10.1007/bf03345068
|View full text |Cite
|
Sign up to set email alerts
|

Use of the dopamine agonists bromocriptine and cabergoline in the management of risperidone-induced hyperprolactinemia in patients with psychotic disorders

Abstract: Risperidone is a novel antipsychotic agent that blocks both dopaminergic and serotonergic receptors. In several reports, clinically significant hyperprolactinemia has been reported in patients on this agent. However, the optimal management of risperidone-induced hyperprolactinemia has not been clarified. We reviewed the records of 5 patients with psychotic disorders who were evaluated for risperidone-induced hyperprolactinemia. There were 4 females and 1 male patient, aged 30-45 yr. All patients had significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
2
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 21 publications
1
33
2
5
Order By: Relevance
“…All of them were short-term and had small sample sizes, as shown in Table 1. [13][14][15][16][17][18][19][20][21][22][23][24][25] Bromocriptine was involved in the treatment of these dysfunctions in two studies, sildenafi l in four, amantadine in two and cyproheptadine, imipramine, shakuyaku-kanzo-to, cabergoline and selegiline in one each.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All of them were short-term and had small sample sizes, as shown in Table 1. [13][14][15][16][17][18][19][20][21][22][23][24][25] Bromocriptine was involved in the treatment of these dysfunctions in two studies, sildenafi l in four, amantadine in two and cyproheptadine, imipramine, shakuyaku-kanzo-to, cabergoline and selegiline in one each.…”
Section: Resultsmentioning
confidence: 99%
“…Dopamine agonists such as bromocriptine and cabergoline may be successful in reducing the level of hyperprolactinemia and alleviating symptoms in some patients. 15 Previous studies 14 have shown that modest doses of bromocriptine may be safely prescribed to patients taking older fi rst-generation agents, and who have symptomatic hyperprolactinemia without exacerbating psychosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…68 Dopamine agonists are sometimes used, although there are reports that these agents can precipitate psychosis in predisposed patients. [69][70][71][72][73] In subjects not seeking fertility, sex steroid replacement in the form of oestrogen (or testosterone in males) may be appropriate, particularly for women of pre-menopausal age with amenorrhoea. 26 If the patient is largely asymptomatic, no specific treatment may be necessary.…”
Section: B U S I N E S S B R I E F I N G : E U R O P E a N E N D O C mentioning
confidence: 99%
“…Switching from a prolactinelevating antipsychotic to olanzapine has been reported to restore normal sexual function (84). Other clinicians have reported that coadministration of dopamine agonists such as bromocriptine and cabergoline may reverse antipsychoticinduced sexual dysfunction (85,86).…”
Section: Antipsychoticsmentioning
confidence: 99%